Bilateral benign giant phyllodes tumor in an adolescent female: a rare case report - Bhasin, Sanjay Kumar; Kumari, Sunita; Kumar, Vijay; Saini, Paras; Sharma, Gopal; Akram, Mubashir (International Surgery Journal, 2016)
Cystosarcoma phyllodes or phyllodes tumor are rare fibroepithelial neoplasm accounting for only about 1% of the breast lesions in children and adolescents. Whether benign, borderline or malignant, they have high potential of recurrence. These biphasic tumors are having very low rate of bilateral occurrence and in that event they tend to be asynchronous. The definitive treatment of the benign entity is either wide local excision or mastectomy depending upon size and age of the patient. Ours is a case of 16 years old, orphan low socio-economic status female having bilateral giant phyllodes tumors that were confirmed on Fine needle aspiration cytology of both breasts. Wide local excision of the tumor could be done on the right side, and patient was discharged on 10th post-operative day with advice to report after 6 weeks for possible surgery on the left enlarged breast. The histopathology report was consistent with the findings of benign phyllodes of the breast. Patient reported for the second surgery after 10 months of the first surgery and was subjected in wide local excision on the left side also. The case under report finds rarity due to its huge size, bilateral presentation in an unmarried adolescent female where the decision making regarding its definitive management becomes extremely difficult.